Diagnosis, patogenesitas dan pemeriksaan Campylobacter jejuni - Conny Riana Tjampakasari; Siti Kusmaryeni (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2021)
Campylobacterosis is an infection disease caused by bacteria from Campylobacter genus, especially Campylobacter jejuni (C. jejuni) species. This Gram-negative bacteria has very mall size, rod-shaped, thin and some are spiral shaped. C. jejuni does not have spore, catalase positive, nitrat reductor, and highly motile with flagella located at one or two ends of its body. It’s growth is microaerophilic, grow optimally with low oxygen levels. In the growth media, all Campylobacter sp grew well at pH 5.5-8.0. Colonies appear round, smooth and convex. Campylobacteriosis is zoonotic, which mean it can be transmitted from animals to humans. Bacteria that enter the human body produce a toxin, Cytolethal Distending Toxin (CDT), which is one of the pathogenic factors. Clinical manifestations caused diarrhea, sometimes to bloody, abdominal pain, fever, nausea and vomiting. In humans and animals, most cases are asymptomatic. Laboratory tests to support a definite diagnosis of infection by Campylobacteriosis are necessary. Based on this, the purpose of writing this article is to link the diagnosis and pathogenesis of Campylobacteriosis with microbiological examination. Microbiological examinations that can be done are microscopic, culture and non-culture. Currently, non-culture techniques being developed include Polymerase Chain Reaction (PCR), Epidemiological typing system and serology.